2017
DOI: 10.1016/j.jcot.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcome of pilon fractures managed with limited internal fixation and external fixation: A prospective clinical study

Abstract: The technique of combined external fixation with internal fixation is safe and effective management option for intra-articular distal tibial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
15
0
2
Order By: Relevance
“…First, the two therapies presented similar infection rates, indicating that the additional LIF did not lead to increased infection risks, even in Gustilo-Anderson grade II or IIIA fractures, as long as thorough debridement and adequate soft tissue coverage were performed. A similar conclusion can be obtained from the experience of treating other open injuries, especially intra-articular tibial fractures [2527]. Along with external fixation, limited internal fixation can offer sufficient stability and may decrease the incidence of subsequent reduction loss.…”
Section: Discussionsupporting
confidence: 60%
“…First, the two therapies presented similar infection rates, indicating that the additional LIF did not lead to increased infection risks, even in Gustilo-Anderson grade II or IIIA fractures, as long as thorough debridement and adequate soft tissue coverage were performed. A similar conclusion can be obtained from the experience of treating other open injuries, especially intra-articular tibial fractures [2527]. Along with external fixation, limited internal fixation can offer sufficient stability and may decrease the incidence of subsequent reduction loss.…”
Section: Discussionsupporting
confidence: 60%
“…Some surgeons believe that EFLIF can achieve similar functional outcomes in open distal tibia fractures and shorten the operation and fracture healing times [19][20][21]. Meena et al suggested that combined external and internal xations were a safe and effective management option for intra-articular distal tibial fractures [22]. Therefore, we concluded that using limited internal xation could provide enough stability, cannot be replaced by internal xation, and presents a lower infection risk than it.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding infection, in our series, there were 11 cases of pin tract infections, which is a well-recognised complication associated with external fixation around the ankle. 12 In metaanalysis by Papadokostakis et al, minor and major infection was observed in 11.7% and 3.9% cases respectively, treated with ankle spanning fixator with or without minimally invasive techniques. 1 Complication rate, mainly infection and wound dehiscence, was found higher (17%) in patients with ORIF, as reported by Mcferran et al 20 The incidence of osteoarthritis following tibial pilon fractures varies in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Temporary stabilization with K-wires also allows an intra-operative check with a C-arm image intensifier, before a definitive stabilization by screws is performed. 12 Analysing existing literature on this topic must be delicate because most studies refer to a heterogeneous group of patients that include type A and B injuries. 10 Davidovitch et al retrospectively compared between external fixation and ORIF and concluded that the overall complication and union rates as well as functional outcomes were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%